OCVIRKOVA TEZA O KONSTRUKTIVIZMU PRI KOSOVELU (Filološke pripombe, 2019)
A large part of Kosovel's affiliation to the historical avantgarde was ascribed by Anton Ocvirk to constructivism thereby emphasizing that Kosovel was never partial to "pure abstraction". A close reading of Kosovel's poetry, diary and correspondence, confirms the thesis of the influence of Russian literary constructivism which justifies Ovirk's judgement.